Spatial modeling of basal area and tree volume in managed Pinus patula and P. teocote forests in the ejido Atopixco, Hidalgo - Cruz-Leyva, Isidro Ahmed; Valdez-Lazalde, José René; Ángeles-Pérez, Gregorio; de los Santos-Posadas, Héctor Manuel (Instituto de Ecología, A.C., 2016)
Basal area (AB m2/ha) and tree volume (VOL m3/ha) were modeled for even-aged Pinus patula and P. teocote forest stands located in Hidalgo, Mexico. Variables such as tree crown cover (COB), field recorded Leaf Area Index (LAI5 m2/m2), allometric Leaf Area Index (LAIAL m2/m2) ; GIS variables and reflectance data derived from a multispectral SPOT 5  image were used as independent variables. Environmental conditions were characterized by digitizing the INEGI’s chart of climatic effects (scale 1: 250 000) and processing the Digital Elevation Model (MDE) of the study area. A geographic information system (GIS) was set up with variables such as Elevation, Slope’s angle and aspect, Temperature, Precipitation, SPOT derived spectral bands, and two sets of vegetation indices based either on a) the ratio of spectral bands (NDVI and CTVI) or on b) the spectral distance between vegetation and bare soil (PVI and SAVI). Multiple linear regression models were fitted based on field and GIS data. AB was significantly related to LAIAL, Mean Annual Temperature (TMA), ALTITUD and SPOT Band 4 reflectance (P < 0,001, R2 = 0,9662). VOL was significantly related to LAIAL, Mean Annual Temperature (TMA) and ALTITUD (P < 0,001, R2 = 0,8856).